Tracking finance for locally led climate action in Ethiopia: Existing initiative, challenges and recommendations - Callaghan, Charles; Binge, Brenda; Tesfaye, Lidya; Jalango, Dorcas; Chilambe, Pedro; Lauriciano, Rabeca (2025)
This report assesses how climate finance for locally led climate action is tracked and reported in Ethiopia, and outlines steps to improve transparency and accountability. It notes Ethiopia’s high climate vulnerability and the dominance of AFOLU emissions, alongside large investment needs under NDC 3.0. A central challenge is that international reporting systems often show only first recipients (e.g., national ministries or international agencies), offering limited visibility on whether finance reaches regions, woredas, and communities. The report argues that tracking should capture both the amount of funding reaching subnational actors and the quality of finance, including subsidiarity, flexibility, patience, and predictability. Key gaps include fragmented donor requirements, inconsistent definitions, limited capacity, and underreporting of NGO and recurrent spending. Recommendations include strengthening national repositories (e.g., via the CRGE Facility), harmonizing templates and taxonomies, improving MRV/verification, and expanding subnational tagging to track commitments and disbursements.